Effective nitrogen removal in a granule-based partial-denitrification/anammox reactor treating low C/N sewage. (February 2020) - Xu, Xinxin; Ma, Bin; Lu, Wenkang; Feng, Dianbao; Wei, Yan; Ge, Chengjun; Peng, Yongzhen
Highlights: A granule-based partial-denitrification/anammox (PDA) process was developed. Granules were formed with an average particle size of 1.92 mm. The two most abundant genera in granules were Thauera and Candidatus Brocadia . Nitrogen was effectively removed via PDA with the COD/TN ratio of 1.52. 90% of dinitrogen was produced by anammox bacteria in the PDA reactor. Abstract: The partial-denitrification/anammox (PDA) process is a promising method to achieve mainstream anammox in wastewater treatment plants (WWTPs). To investigate the feasibility of developing a granule-based process for effective nitrogen removal via PDA, an upflow anaerobic sludge bed reactor was used as a PDA reactor treating low C/N sewage for over 200 days. Granules were formed with an average particle size of 1.92 mm. Metagenomic analysis revealed that the two most abundant genera in granules were Thauera (17.46%) and Candidatus Brocadia (6.24%) which played important roles in achieving partial-denitrification and anammox, respectively. Effective nitrogen removal was achieved with an average effluent TN concentration of 8.74 mg/L when influent TN concentration and COD/TN ratio were 42.56 mg/L and 1.52, respectively. Nitrogen removal via anammox accounted for 90% of dinitrogen production in the PDA reactor. Finally, a granule-based combined process of PDA with nitrification was proposed for achieving anammox in mainstream WWTPs.